Practicality of a batak toba culture-based realistic model in the higher-order thinking skills of pre-service elementary school teachers - Patri Janson Silaban; Anton Sitepu; Israil Sitepu (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
This study evaluates the practicality of a Realistic Mathematics Education model integrated with Batak Toba cultural elements to develop Higher-Order Thinking Skills among pre-service elementary school teachers. Using a Research and Development (R&D) design based on Plomp’s three-phase model, the research involved preliminary investigation, design and development, and evaluation. The model was validated through expert judgment, pilot testing, and classroom trials. Practicality was assessed using indicators of implementation, ease of use, student engagement, and practitioner acceptance. Results from two trials showed significant improvements: implementation increased from 3.2 to 4.5, lecturer ease from 3.1 to 4.4, student engagement from 3.0 to 4.3, and practitioner acceptance from 3.3 to 4.6 (scale 1–5). Students’ HOTS improved from a moderate category (0.63) in the first trial to a high category (0.85) in the second. These findings indicate that the Batak Toba culture-based RME model is practical, culturally relevant, and pedagogically effective, with strong potential for integration into teacher education programs.